2017
DOI: 10.1111/bcpt.12712
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance Skills, Knowledge and Attitudes in our Future Doctors – A Nationwide Study in the Netherlands

Abstract: Pharmacovigilance centres monitor the safety of drugs, based on adverse drug reactions (ADRs) reported by doctors, pharmacists and pharmaceutical companies. However, the under-reporting of ADRs remains a major problem. Our aim was to investigate preparedness of future doctors for their role in pharmacovigilance, by assessing their pharmacovigilance awareness, skills and knowledge. The study was a nationwide e-survey among medical students (third to sixth year) of all eight medical schools in the Netherlands. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 23 publications
3
41
1
Order By: Relevance
“…The median number of students per study was 104 (range 1–2413). Besides final‐year medical students, some studies also involved 1–5th year students ( n = 20) 24, 25, 26, 28, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, junior doctors and residents ( n = 8) 25, 28, 33, 46, 47, 48, 49, 50, medical specialists ( n = 2) 48, 50, pharmacy students ( n = 3) 32, 51, 52, dental students ( n = 2) 31, 41 and nonhealthcare students ( n = 1) 40.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of students per study was 104 (range 1–2413). Besides final‐year medical students, some studies also involved 1–5th year students ( n = 20) 24, 25, 26, 28, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, junior doctors and residents ( n = 8) 25, 28, 33, 46, 47, 48, 49, 50, medical specialists ( n = 2) 48, 50, pharmacy students ( n = 3) 32, 51, 52, dental students ( n = 2) 31, 41 and nonhealthcare students ( n = 1) 40.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies showed that students had a positive attitude to pharmacovigilance but lacked knowledge about where and how to report adverse drug reactions 30, 41, 43, 45, 47, 83. Although many students (27–80%) had encountered an adverse drug reaction during clinical clerkships, very few (1–18%) had reported one 30, 43.…”
Section: Resultsmentioning
confidence: 99%
“…This may include ongoing training and education at pre-service and in-service levels, involvement of Therapeutic Committees at facility and regional levels and introduction, for example, of innovative electronic reporting to improve efficiency and boost the response rate among healthcare workers. [19][20][21][22] In conclusion, the study revealed a high level of knowledge of pharmacovigilance and ADR reporting system among the healthcare workers, though this has informed neither their attitude nor their practice of ADR reporting as seen in their reported attitude and practice. In other to optimize the current system, there is a need for effective communications between TIPC and the healthcare workers; this may be in the form of feedback, continuing professional development (CPD) lectures, advocacy within the health sector and community engagement.…”
Section: Community Engagementmentioning
confidence: 74%
“…Depending on the setting, centralized, national reporting systems may not always be the solution to pharmacovigilance but if they are adopted—as is the case in Namibia—there is a need to continually support their function and improvement. This may include ongoing training and education at pre‐service and in‐service levels, involvement of Therapeutic Committees at facility and regional levels and introduction, for example, of innovative electronic reporting to improve efficiency and boost the response rate among healthcare workers …”
Section: Discussionmentioning
confidence: 99%
“…Undergraduate pharmacy education on PV and ADR reporting is important to foster the right attitude in pharmacists, who have an important role in patient safety. To date, very few studies have targeted students when evaluating the factors contributing to reporting intent . Importantly, this study determined the predictive factors for intent to report ADR with the aim of developing strategies to improve PV education.…”
Section: Discussionmentioning
confidence: 99%